MSCs engineered with secreted Klotho alleviate blood–brain barrier disruption and reduce neuroinflammation more effectively than MSCs in experimental autoimmune encephalomyelitis - Narges Maleki; Maryam Rezapour Kalkhorann; Mohammad Sajad Sajad Emami Aleagha; Amir Emami; Abdolamir Allameh (Stem Cell Research & Therapy)
Abstract Background The anti-aging protein, Klotho, has been shown to exert neuroprotective effects in neurodegenerative disorders. This study was designed to evaluate the effects of MSCs engineered with secreted Klotho (SKL-MSCs) on neuroinflammation in experimental autoimmune encephalomyelitis (EAE) mouse model and to investigate underlying molecular mechanisms. Methods EAE was induced in female C57BL/6 mice, and animals were then randomized to receive PBS, MSCs, or SKL-MSCs at the onset of disease. BBB permeability assay was performed. The mRNA and protein expression of inflammatory factors was detected in the brain of animals by real-time PCR and immunohistochemistry, respectively. The mRNA and protein expression of BBB-associated factors was detected in the brain of animals by real-time PCR and Western blotting, respectively. Results The results showed that SKL-MSCs slowed EAE progression and attenuated the disease severity more effectively than MSCs. SKL-MSCs also decreased the expression of TNF-α, IFN-γ, and IL-17 but increased the expression of IL-10 more potently than MSCs in the brain of EAE animals. Furthermore, SKL-MSCs reduced BBB permeability more significantly than MSCs, which was accompanied by decreased levels of BBB-associated factors, ICAM-1, VCAM-1, MMP-9, and CCL2, in the brain of EAE animals. However, in mice treated with MSCs, the reduction in the expression of BBB-associated factors was limited to ICAM-1 and MMP-9. Conclusions Our study highlighted the significantly greater therapeutic power of SKL-MSCs compared with MSCs in attenuating EAE disease severity and reducing neuroinflammation, which might be mediated through a more marked reduction in the BBB permeability and BBB-associated factors expression levels in the brain of animals.